RANCANG BANGUN ALAT WATERBATH DI LENGKAPI SENSOR SUHU MENGGUNAKAN MIKROKONTROLER ATMEGA328 - Okky Wahyu Arsa; Fitria Priyulida (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2021)
The purpose of designing this tool is to develop a water bath device beforehand so that it can be controlled from the display when it is set using an ATMEGA 328 microcontroller equipped with a temperature sensor and to carry out testing and measuring tools, with temperature selection from 30 C to 90 C, at Previous research was only able to adjust the temperature from 37 C to 60 C and this tool is also more flexible, the temperature sensor in this water bath tool uses the DS18B20 sensor which functions to find out the temperature in this tool. The desired temperature and timer will then be visible on the LCD display then the buzer will sound to indicate the process is complete.The method used in this research is experimentation with system design, tool testing and conclusion drawing. but before doing the design, the timer test is measured 6 times using a stopwatch at a temperature of 50 C and gets an average time of 305 results. 605, and 905 seconds and temperature testing was measured 6 times using a comparison of the thermometer temperature at 5 minutes and the average temperature results were 35.11 C, 45.11 C, 55.11 C, and 65.11 C , Based on data collection that has been done using a stopwatch and thermometer comparison, this water bath device can produce the desired temperature. The ability of this tool can withstand a maximum temperature of 90 C.